Performance evaluation of pervious geopolymer concrete incorporating recycled concrete aggregate - Faiz Habib Anwar; Hilal El-Hassan; Mohamed Hamouda; Abdulkader El-Mir; Kim Hung Mo (International Journal of Sustainable Engineering)
This study aims to evaluate the physical, mechanical, permeability, and durability characteristics of pervious geopolymer concrete (PGC) made with recycled concrete aggregates (RCA), blast furnace slag (GGBS), and fly ash (FA). PGC mixes were formulated to attain two design porosities, 10 and 15%, using two binder combinations of GGBS:FA at ratios of 1:0 and 1:1. Natural coarse aggregates (NCA) were substituted with up to 100% RCA. Hardened density, porosity, compressive, splitting tensile, and flexural strengths, permeability, and abrasion resistance were determined. Results showed that PGC mixes had superior or comparable performance to the control mix made with cement and NCA. The incorporation of RCA or FA into the PGC mix reduced the hardened density, strengths, and abrasion resistance, while increasing porosity and permeability. The combined effect of FA inclusion and higher design porosity of 15% intensified the reduction in performance. The clogging and permeability restoration potential were evaluated after a simulated 20-year exposure to clogging materials. Despite permeability losses reaching 71% due to clogging, nearly 94% of the initial permeability could be restored through pressurised water washing. Research findings highlight the ability to valorise GGBS, FA, and RCA in the production of a cement-free PGC for use in pavement applications.